A New Conjugate Gradient Coefficient for Unconstrained Optimization Based On Dai-Liao - Ibrahim, Alaa L.; Sadiq, Muhammad A.; Shareef, Salah G. (Science Journal of University of Zakho, 2019)
This paper, proposes a new conjugate gradient method for unconstrained optimization based on Dai-Liao (DL) formula; descent condition and sufficient descent condition for our method are provided. The numerical results and comparison show that the proposed algorithm is potentially efficient when we compare with (PR) depending on number of iterations (NOI) and the number of functions evaluation (NOF).